2018
DOI: 10.1073/pnas.1803443115
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -activated Cl current predominates in threshold response of mouse olfactory receptor neurons

Abstract: In mammalian olfactory transduction, odorants activate a cAMP-mediated signaling pathway that leads to the opening of cyclic nucleotide-gated (CNG), nonselective cation channels and depolarization. The Ca influx through open CNG channels triggers an inward current through Ca-activated Cl channels (ANO2), which is expected to produce signal amplification. However, a study on an mouse line reported no elevation in the behavioral threshold of odorant detection compared with wild type (WT). Subsequent studies by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
14
1
Order By: Relevance
“…We crossed heterozygous Ano2 -/+ mice (see Methods; Li et al, In Review 24 ) with a mouse strain that expresses the Ca 2+ indicator GCaMP3 in all ORNs (OMP-GCaMP) 25 to obtain two groups of mice, Ano2 -/- /OMP-GCaMP3 (KO) and Ano2 +/+ /OMP-GCaMP3 (WT). First we used wide-field epifluorescence imaging to obtain functional maps of activated glomeruli for seven monomolecular odors by measuring odor-evoked increases in GCaMP fluorescence at ORN axon terminals 26 .…”
Section: Resultsmentioning
confidence: 99%
“…We crossed heterozygous Ano2 -/+ mice (see Methods; Li et al, In Review 24 ) with a mouse strain that expresses the Ca 2+ indicator GCaMP3 in all ORNs (OMP-GCaMP) 25 to obtain two groups of mice, Ano2 -/- /OMP-GCaMP3 (KO) and Ano2 +/+ /OMP-GCaMP3 (WT). First we used wide-field epifluorescence imaging to obtain functional maps of activated glomeruli for seven monomolecular odors by measuring odor-evoked increases in GCaMP fluorescence at ORN axon terminals 26 .…”
Section: Resultsmentioning
confidence: 99%
“…The mucus composition is fundamental to maintain the ionic environment necessary for olfactory transduction. Indeed, the binding of odorant molecules to odorant receptors in the cilia of olfactory sensory neurons leads to a transduction cascade that includes the activation of CNG channels and the Ca 2+ -activated Cl − channels TMEM16B, whose function depends on the Cl − electrochemical gradient between the mucus and the intraciliary compartment (Pifferi et al, 2009; Stephan et al, 2009; Billig et al, 2011; Pietra et al, 2016; Dibattista et al, 2017; Neureither et al, 2017; Li et al, 2018; Zak et al, 2018; Reisert and Reingruber, 2019). Thus, the Cl − concentration regulated by TMEM16A would affect the TMEM16B-mediated current, modifying the odorant response of the olfactory sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, two successive studies, using the same ANO2-knockout mouse, reported some abnormalities in the olfactory behavior and the olfactory wiring of these animals (234,235) and thus substantially weakened the functional significance of the study of Billig and coworkers (233). Furthermore, two recent studies, using frog and mouse ORNs, emphasized the pivotal role of the Cl À current in signal amplification in ORNs (236,237). Pietra and coworkers in their work convincingly showed that the Ca 21 -activated Cl À channels of ORNs profoundly affected both their glomerular targeting in the OB and their electrophysiological responses.…”
Section: Transduction Mechanisms In Receptor Neuronsmentioning
confidence: 99%